Impact of salt reduction on bread on sensory preference and physicochemical parameters - Monteiro, C (2021)
Purpose The purpose of this study was to evaluate the impact of salt reduction on bread physicochemical parameters and sensory analysis. The relationship between sensory attributes and preference was assessed using external preference mapping (PREFMAP). Moreover, sensory attributes relationship with physicochemical parameters was evaluated. Methodology Four Portuguese bread formulations were tested: Dâgua, Carcaça, Mistura, and Regueifa, produced with different salt concentrations (0.0%, 0.8%, 1.0%, 1.1%, 1.3%, and 1.4% of salt per wheat flour). Bread physicochemical characteristics evaluated included weight, volume, moisture, salt content, and crumb colour and structure. Sodium was determined by flame photometry method, while crumb colour and structure by digital image analysis. Sensory analysis was carried out with 8 trained assessors and consumer test with 80 participants. Statistical models for sensory preference evaluation were developed using PREFMAP. Statistical comparison was performed using as control bread with 1.4% of salt (legal value allowed). Findings Overall, salt reduction had significant impact on moisture, salt content and colour parameters, but limited influence on crumb morphology. Salt reduction had a significant negative impact on overall assessment, taste liking and overall linking attributes. The lowest salt concentrations with best consumer acceptance were: 0.8% (D'Agua and Carcaça), 1.0% (Mistura), and 1.1% (Regueifa). These results suggest that salt reduction in these breads is possible without major impact on bread characteristics and without compromising consumers acceptance.